Unraveling Muscle Impairment Associated With COVID-19 and the Role of 3D Culture in Its Investigation - Seixas, Maria Luiza G. A.; Mitre, Lucas Pari; Shams, Shahin; Lanzuolo, Gabriel Barbugian; Bartolomeo, Cynthia Silva; Silva, Eduardo A.; Prado, Carla Maximo; Ureshino, Rodrigo; Stilhano, Roberta Sessa (Frontiers in Nutrition, 2022)
COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been considered a public health emergency, extensively investigated by researchers. Accordingly, the respiratory tract has been the main research focus, with some other studies outlining the effects on the neurological, cardiovascular, and renal systems. However, concerning SARS-CoV-2 outcomes on skeletal muscle, scientific evidence is still not sufficiently strong to trace, treat and prevent possible muscle impairment due to the COVID-19. Simultaneously, there has been a considerable amount of studies reporting skeletal muscle damage in the context of COVID-19. Among the detrimental musculoskeletal conditions associated with the viral infection, the most commonly described are sarcopenia, cachexia, myalgia, myositis, rhabdomyolysis, atrophy, peripheral neuropathy, and Guillain-Barré Syndrome. Of note, the risk of developing sarcopenia during or after COVID-19 is relatively high, which poses special importance to the condition amid the SARS-CoV-2 infection. The yet uncovered mechanisms by which musculoskeletal injury takes place in COVID-19 and the lack of published methods tailored to study the correlation between COVID-19 and skeletal muscle hinder the ability of healthcare professionals to provide SARS-CoV-2 infected patients with an adequate treatment plan. The present review aims to minimize this burden by both thoroughly exploring the interaction between COVID-19 and the musculoskeletal system and examining the cutting-edge 3D cell culture techniques capable of revolutionizing the study of muscle dynamics.